Persistent Hiccups as an Atypical Presentation of SARS-CoV-2 Infection: A Systematic Review of Case Reports - Giannos, Panagiotis; Katsikas Triantafyllidis, Konstantinos; Geropoulos, Georgios; Kechagias, Konstantinos S. (Frontiers in Neurology, 2022)
Symptoms such as fever, dry cough, dyspnoea, and respiratory distress are commonly described in patients infected with Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Recently, a growing number of cases pertained to persistent hiccups have been reported by SARS-CoV-2 infected patients. The aim of this systematic review was to screen the current literature and provide a summary of the reported cases of SARS-CoV-2 infected patients presenting with persistent hiccups. The PubMed, Scoups and Web of Science databases were searched according to PRISMA guidelines from inception until 1, 2020 and December 31, 2020. Case reports or case series that provided a separate clinical description for patients with presenting complaints of persistent hiccups before or after COVID-19 diagnosis, were retrieved. The critical appraisal checklist for case reports provided by the Joanna Briggs Institute (JBI) was employed to evaluate the overall quality of the eligible studies. We identified 13 eligible studies that included 16 patients in which presenting complaints of hiccups were reported by hospitalised and emergency department-admitted COVID-19 patients. The mean duration of hiccups was 4.6 days reported in 87% (14/16) patients. Hypertension was the most common comorbidity present in 50% (8/16) of patients followed by diabetes mellitus (4/16). Moreover, 43% (7/16) of patients received only one medication for managing the hiccups with metoclopramide (5/16) followed by chlorpromazine and baclofen (4/16) used as primary treatment. Equally, 43% of patients (7/16) received dexamethasone followed by azithromycin (5/16), ivermectin (4/16) and ceftriaxone (4/16) for managing the infection from SARS-CoV-2. The majority of patients (14/16) improved after initiation of treatment. Persistent hiccups are possibly a rare symptom clinicians may expect to encounter in patients infected with SARS-CoV-2. Although there is not ample proof to propose causation, increased awareness about the diversity of presentations of SARS-CoV-2 infection, could be crucial in the early recognition of the disease.